DISPOSAL OF GROUP A WASTE: WHAT HAS CHANGED? (CIPEEX, 2022)
HEALTH SERVICES WASTE (SSR) IS ALL WASTE RESULTING FROM ACTIVITIES CARRIED OUT BY ESTABLISHMENTS RELATED TO HUMAN OR ANIMAL HEALTH. THE FIRST RESOLUTION OF THE RDC COLLEGIAL BOARD NO. 306 OF THE YEAR 2004 AND THE PURPOSE WAS TO ESTABLISH THE PROCEDURES IN THE SERVICES OF GENERATORS OF WASTE IN ORDER TO RECONCILE WITH THE RESOLUTION OF CONAMA 358/2005. IN 2010 THERE WAS PUBLICATION OF LAW NO. 12,305, DISPOSING OF THE NATIONAL SOLID WASTE POLICY, SINCE THEN DRC NO. 306 HAS RECEIVED SEVERAL CRITICISMS. THUS, THIS YEAR DRC NO. 306 HAS BEEN REVISED AND REPLACED BY DRC NO. 222 WHICH REGULATES GOOD PRACTICES IN THE MANAGEMENT OF HEALTH CARE WASTE. GROUP A RSSS ARE CHARACTERIZED BY THE POSSIBLE PRESENCE OF BIOLOGICAL AGENTS AND MAY PRESENT RISKS. GROUP A IS SUBCLASSIFIED FROM A1 TO A5 IN RESPECT OF THE PARTICULARITIES FOR EACH RESIDUE GENERATED IN THE CLINICAL LABORATORY. THE CLINICAL LABORATORY PRODUCES RESIDUES OF SUBGROUP A1. THE OBJECTIVE WAS TO EVALUATE THE CHANGES MADE FROM DRC NO. 306 TO DRC NO. 222, IN CLASS A- (A1) COVERING THE MAIN RESIDUES PRODUCED BY THE CLINICAL ANALYSIS LABORATORY. IT IS A COMPARATIVE REVIEW STUDY, AFTER THE READING OF THE RESOLUTIONS WERE OBSERVED AND NOTED THE CHANGES REGARDING THE TREATMENT OF RESIDUES BELONGING TO GROUP A1. THE RESIDUES WERE LEFTOVER LABORATORY SAMPLES CONTAINING BLOOD OR BODY FLUIDS, CULTURES AND STOCKS OF CULTURE MEDIA, CULTURE MEDIA AND INSTRUMENTAL FOR TRANSFER OR BLENDING OF MICROORGANISM STOCK CULTURES. RDC NO. 306 OF 2004 PROVIDES THAT LABORATORY SAMPLE LEFTOVERS CONTAINING BLOOD OR BODY FLUIDS SHOULD BE SUBJECTED TO TREATMENT PRIOR TO FINAL DISPOSAL. IN CONTRAST, RDC NO. 222 OF 2018 IN ART. 49 § 1, STATES THAT LEFTOVER LABORATORY SAMPLES CONTAINING BLOOD OR BODY FLUIDS MAY BE DISPOSED OF DIRECTLY IN THE SEWAGE COLLECTION SYSTEM, PROVIDED THAT THEY RESPECTIVELY MEET THE RULES ESTABLISHED BY THE ENVIRONMENTAL AGENCIES AND BY THE COMPETENT SANITATION SERVICES, WITHOUT REQUIRING TREATMENT, DIRECTLY DISPOSING OF THE SEWAGE SYSTEM. NOTE IN DRC NO. 222 WAS A DISAGREEMENT BETWEEN ARTICLE 49 AND PARAGRAPH 1 THEREOF, WHILE ARTICLE 49 STATES THE NEED TO TREAT LEFTOVER BLOOD AND BODY FLUIDS BEFORE FINAL DISPOSAL, PARAGRAPH 1 CONFERS FREEDOM TO RSS BE DISCARDED IN AN UNTREATED SEWAGE NETWORK, GENERATING A DIFFICULTY IN THE INTERPRETATION AND UNDERSTANDING OF THE TEXT, AND THERE IS A NEED FOR COURSES OFFERED BY ANVISA, IN ORDER TO CLARIFY THE NEW REGULATIONS. CULTURES AND STOCKS OF CULTURE MEDIA, CULTURE MEDIA AND INSTRUMENTAL FOR TRANSFER OR BLENDING OF CULTURES OF MICROORGANISMS STOCKS. THEY MUST BE SUBMITTED TO TREATMENT, USING PROCESSES THAT ARE VALIDATED TO OBTAIN REDUCTION OR ELIMINATION OF THE MICROBIAL LOAD, WITH NO MODIFICATION IN BOTH RDC'S NO. 306 AND NO. 222. IN VIEW OF THIS, IT CAN BE OBSERVED THAT THERE WERE SMALL ALTERATIONS BETWEEN THE NORMS IN RELATION TO THE DISPOSAL OF THE SUBGROUP A1 IN THE RESIDUES GENERATED IN CLINICAL LABORATORY.
Keywords: Medical Waste; Clinical Laboratory Techniques; Blood